المعجم السّياحي ودوره في التنمية السّياحية الثقافية المستدامة بين المشهود والمنشود - عيشون, خيرة; هدنة, خالد (جامعة الوادي - University of Eloued, 2019)
ملخص: تُشكّل السّياحة محرّكا رئيسا لدفع عجلة التنمية، والنّمو، وهي المحور الأساسي في قطاع الخدمات بسبب قدرتها على تكوين الثروة، ومنح فرص العمل، وقد أضحت السّياحة اليوم من معايير تقدم الدّول في العديد من المجالات الثقافية والاقتصادية والاجتماعية... لمالها من سمات إيجابية، فهي الوسيلة الحضارية لنقل وتبادل الثقافات بين شعوب العالم المختلفة، حيث تنتقل المعتقدات والفنون والتراث ومختلف ألوان الثقافة عن طريق الحركة السّياحية، وليس من وسيلة لتحقيق هذا الهدف إلاّ اللّغة باعتبارها الأداة الفاعلة على إنجاح السّياحة الثقافية، وهذا يثير في الذهن مجموعة من التّساؤلات لعل أهمّها. ما مدى وظيفة اللّغة العربية في القطاع السياحي؟ هل استعمال العربية يجذب السائح أم ينفّره؟ كيف يخدم المعجم السياحي التنمية الثقافية؟ Abstract : Tourism is a major driver for development and growth, it is the main focus in the services sector, because of its ability to generate wealth and employment opportunities. Tourism today has become a progress criteria standards for countries in many cultural, economic and social fields, because of its positive features, it is the means of civilizational to transfer and exchange of cultures among different peoples of the world, where beliefs, arts, heritage and various types of culture are transmitted through the tourist dynamics; no other method but language can achieve this objective, being an effective tool to the success of cultural tourism, this brings to mind a whole set of questions, the most important one being: to what extent is the function of the Arabic language in the tourism sector? does the use of Arabic attracts tourists or alienate them? How does the tourism lexicon serve the cultural development? Keywords: Tourism, Tourism lexicon, Cultural Development, Arabic Language, Sustainable Development
مقال
Keywords: السياحة، المعجم السياحي، التنمية الثقافية، اللغة العربية، التنمية المستدامة